Social capital, proximity and team performance improvement - Jakub Wojnar (European Regional Science Association (ERSA), 2010)
Social capital, proximity and team performance improvement Jakub Wojnar Ph.D. student of the Systems Research Institute of the Polish Academy of Sciences ul. Newelska 6, 01-447 Warsaw, Poland email: jakub@wojnar.info The purpose of this paper is twofold. The first part translates some theoretical concepts of social capital into business terms and explains its daily usage in international corporations. The second and main objective of the paper is a description of a method of recruiting new members to the team working on the Virtual Production Line (VPL) the concept introduced by Walukiewicz in 2006. The core idea of the method is based on the assumption that the new hire should possess appropriate expertise knowledge (cognitive proximity) as well as the team adjustment ability (emotive proximity). In other words, teamwork capabilities of the team - either existing or new - are at least equally important as knowledge of individual members. Thus, the team development model is based on the combination of different forms of proximity in its optimised way. The first stage of the method focuses on analysis of existing team members in terms of team role types (i.e. Belbin team roles, Myer-Briggs typology), existing professional skills (i.e. knowledge domain individual levels), interactions between individuals (i.e. communication channels, formal and informal team leaders), etc. This allows identification of key members and key competences of the team and possible gaps. The second stage of the method is focused on the analysis of potential candidates in order to select the best one. Finally, by using different forms of proximity we are going to improve the performance and productivity of the team working on a particular VPL or solving a particular problem.
Keywords: 330